2015
DOI: 10.5812/aapm.23139
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Epidural Injections in the Treatment of Lumbar Central Spinal Stenosis; A Systematic Review

Abstract: Context:Lumbar central spinal stenosis is common and often results in chronic persistent pain and disability, which can lead to multiple interventions. After the failure of conservative treatment, either surgical or nonsurgical modalities such as epidural injections are contemplated in the management of lumbar spinal stenosis.Evidence Acquisition:Recent randomized trials, systematic reviews and guidelines have reached varying conclusions about the efficacy of epidural injections in the management of central lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 82 publications
0
80
1
2
Order By: Relevance
“…10 11 Interventional spine procedures continue to be used frequently for pain management. Medicare 12 beneficiaries receiving epidurals increased by 106.3% from 1997 to 2006 1. Our study found no 13 increase in the proportion of ESI catastrophic complications requiring acute inpatient 14 rehabilitation between the years 2001-2008 compared to all SCI admissions at our study site.…”
contrasting
confidence: 51%
“…10 11 Interventional spine procedures continue to be used frequently for pain management. Medicare 12 beneficiaries receiving epidurals increased by 106.3% from 1997 to 2006 1. Our study found no 13 increase in the proportion of ESI catastrophic complications requiring acute inpatient 14 rehabilitation between the years 2001-2008 compared to all SCI admissions at our study site.…”
contrasting
confidence: 51%
“…However, among others, debate continues with variable evidence for various pathologies ranging from some evidence of efficacy to a lack of efficacy [2, [49][50]. Utilizing the best evidence synthesis with five levels of evidence [47] with level I evidence denoting consistent findings among multiple high-quality RCTs and level II evidence denoting consistent findings among multiple lowquality RCTs, or one high-quality RCT, the evidence is level II in managing disc herniation with or without steroids in the cervical, lumbar and thoracic spine [40][41][42]44]. There is also a potential superiority for steroids demonstrated in managing lumbar disc herniation with up to 1-year followup compared with local anesthetic alone in the lumbar spine with interlaminar and caudal epidural injections [40,42,51].…”
Section: Prevention Of Complicationsmentioning
confidence: 99%
“…Prevention is threefold: understanding of efficacy, indications and medical necessity; pathoanatomy and mechanism of complications; and safe practices with applications of alternate techniques, alternate drug use and appropriate monitoring. Epidural injections are considered to be efficacious in managing multiple pathologies when administered appropriately with proper indications and medical necessity, with assessment of evidence, based on qualitative best evidence synthesis based on high-quality randomized trials with appropriate assessment and cost utility analysis [40][41][42][43][44][45][46][47][48]. However, there is a lack of trials for thoracic transforaminal epidural injections and a lack of efficacy for cervical transforaminal epidural injections, which are also associated with high risk [2,6,41-42].…”
Section: Prevention Of Complicationsmentioning
confidence: 99%
“…However, they, 17 like Kraeutler et al, 5 have relied heavily on a single flawed randomized trial with inappropriate references 3,8 and have omitted a multitude of studies performed with what we believe is a more relevant design. [9][10][11]13 Transforaminal epidural injections are associated with significant complications, including paraplegia, especially when they are performed utilizing the safe triangle approach with particulate steroids. 1,15,16 These complications can be avoided by using an infraneural approach.…”
Section: Responsementioning
confidence: 99%